Glutathione functionalized mesoporous organosilica conjugate for drug delivery. Issue 61 (13th June 2016) - Hu, Lin-Lin; Zhang, Dan-Dan; Zhang, Yang; Shu, Yang; Chen, Xu-Wei; Wang, Jian-Hua
Abstract : We developed a novel pH-responsive drug delivery system based on permeation-enhancing glutathione (GSH) and pH sensitive polyacrylic acid (PAA) grafted mesoporous organosilica nanocarriers (MONs). Abstract : A novel pH-responsive drug delivery system, based on permeation-enhancing glutathione (GSH) and pH sensitive polyacrylic acid (PAA) grafted mesoporous organosilica nanocarriers (MONs), is developed. PAA grafted MONs are prepared via a facile grafting-to strategy and then GSH is conjugated on the PAA chain via an amidation reaction. The resultant MONs–PAA–GSH conjugate not only shows an efficient drug loading efficiency but also offers a superb binding capability to cell membranes. With doxorubicin hydrochloride (DOX) as a model, a loading efficiency of 43.7% is readily achieved for 1.0 mg mL −1 DOX in 1.0 mL aqueous medium with 1.0 mg of MONs–PAA–GSH conjugate. The ensuing release of DOX from the DOX–MONs–PAA–GSH conjugate is pH-dependent, offering release efficiencies of 70.2% (pH 3.0), 45.5% (pH 5.0) and 16.1% (pH 6.5), within 24 h. The MONs–PAA–GSH conjugate displays favorable cellular uptake properties, minimum cytotoxic effect or excellent biocompatibility in comparison with those for MONs–PAA. It is demonstrated that the MONs–PAA–GSH conjugate serves as a promising platform for building a controlled drug delivery system.